Evaluasi Beberapa Ekotipe Jarak Pagar (Jatropha curcas L.) untuk Toleransi Cekaman Kekeringan - Lapanjang, Iskandar; Purwoko, Bambang S.; Hariyadi, ,; Budi R, Sri Wilarso; Melati, Maya (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
Drought stress in crop  occurs due to imbalance between water supply and demand.  Crop responses to drought stress  depend on their ecotypes.  This study was aimed at examining the tolerance of the physic nut ecotype to drought stress in inceptisol. This study was conducted at Silviculture greenhouse, Forestry Faculty IPB, from September to December 2007. A Completely Randomized Design with two factors was used in the experiment, i.e. water content (80, 60, and 40 % of field capacity) and physic nut ecotypes (Palu, NTB, IP-A, and IP-P) The results showed that (1) drought reduced stem diameter (31.4%), root length (65.49%) and leaf area (72.73%), and decreased plant dry weight (74.83%),(2) tolerance level of the evaluated physic nuts on the drought stress were moderate tolerance (IP-1A, NTB,  Palu) and sensitive (IP- Pakuwon).   Key words:  physic nut, drought stress, tolerance